(untitled) (Scientific journal of the Fergana State University, 2026)
This scientific article analyzes the rules for preserving the purity of the Uzbek language in the digital environment (messengers, social networks, online forums), referred to as the rules of “communication hygiene.” While the internet and social media have expanded the space of communication, they have also intensified the issue of maintaining the purity of national languages. The article examines four main factors that threaten language purity (code-mixing, decline in orthographic literacy, emotionally “harmful” vocabulary, and the loss of critical thinking) and substantiates their impact on linguistic norms based on scientific literature.